2022
DOI: 10.34010/jamika.v12i1.6706
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Influencers : Is The Persona Trustworthy?

Abstract: In today's digital world, people are using social media at a higher rate than ever before. One digital marketing phenomenon is the use of services from a virtual influencer. Virtual influencers are computer-generated models who are becoming increasingly famous on social media. The purpose of the study is to identify and analyze the communication way of virtual influencers in the digital marketing era. The current study uses a literature review method that searches article titles and abstracts in electronic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
2
0
5
Order By: Relevance
“…It also creates an opportunity for more publications. For example, Wibawa et al (2022), conducting a literature review based on the keyword "digital influencer," identified 10 publications. Therefore, we decided to use additional keywords, the definitions of which are presented below:…”
Section: Methodsmentioning
confidence: 99%
“…It also creates an opportunity for more publications. For example, Wibawa et al (2022), conducting a literature review based on the keyword "digital influencer," identified 10 publications. Therefore, we decided to use additional keywords, the definitions of which are presented below:…”
Section: Methodsmentioning
confidence: 99%
“…Tak lama kemudian, fenomena ini turut menarik perhatian Instagram. Instagram sebagai platform jejaring sosial berbasis visual memungkinkan pengguna untuk membuat cerita dan berinteraksi dengan pengikut mereka, memotret gambar, hingga menerapkan filter (Wibawa et al, 2022).…”
Section: Pendahuluanunclassified
“…Belum banyak penelitian yang menyajikan perspektif influencer virtual dari sisi industri. (Wibawa et al, 2022) sebelumnya meneliti tentang perkembangan influencer virtual, baik peluang maupun tantangannya, namun masih menggunakan metode kajian literatur sistematis. Conti et al (2022) juga meneliti mengenai kelebihan, kelemahan, maupun sisi etika influencer virtual, namun hanya fokus kepada sosok influencer virtual itu sendiri.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations